Association of Weight Changes by Three Days after Birth and Mortality and/or Severe Neurological Injury in Preterm Infants < 29 Weeks Gestational Age: A Multicenter Cohort Study - Carlos Zozaya; Khalid Aziz; Nalini Singhal; Xiang Y. Ye; Christine Drolet; Julie Emberley; Kyong-Soon Lee; Vibhuti S. Shah; on behalf of the Canadian Neonatal Network (CNN) (MDPI AG, 2022)
Objective: This study aimed to determine the range of weight loss, at 3 days postnatal age, associated with the lowest risk of mortality/short-term morbidity in preterm infants <29 weeks gestational age (GA). Study design: This multicenter retrospective cohort study employed data from the Canadian Neonatal Network database. The primary outcome was a composite of mortality and/or severe neurological injury. Multivariable quadratic and linear regression models which adjusted for potential confounders were built. Results: A total of 9275 preterm infants (median GA 26, IQR 25, 28 weeks) were included. The optimal weight change range at day three, after adjustment for potential confounders for the primary outcomes, was −15 to −8.9%. Conclusions: There is a 'U'-shaped relationship between weight change from birth to day three and mortality and/or severe neurological injury. Interventional studies, which target weight loss within the range found in this study and evaluate the impact on neonatal outcomes, are needed to corroborate our findings.